Pengaruh Partisipasi Anggaran Dan Budget Emphasis Terhadap Budgetary Slack Dengan Pertimbangan Etika Sebagai Variabel Moderasi - Fadhlurrahman Dwi Febrianto; Noor Endah Cahyawati (Journal of Management and Social Sciences, 2024)
This study aimed to examine the effect of Budget Participation, Budget Emphasis on Budgetary Slack with Ethical Consideration as Moderating Variable. This kind of study is quantitative research with primary data collected in a questionnaire distributed to 38 respondents. The data is processed with multiple linear regression analysis by using Statistical Program for Social Science (SPSS). The results showed that budget participation and budget emphasis has effect on budgetary slack. Meanwhile, ethical considerations cannot moderate the relationship between budget participation and budget emphasis on budgetary slack.